2012
DOI: 10.1115/1.4023086
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Heat Convection Coefficient on Predicted Performance of a Large Tilting-Pad Thrust Bearing

Abstract: Part of the heat generated by the shearing of the lubricating film during operation of a hydrodynamic bearing is transferred to the bearing components. In the case of the pad, which is usually fully submerged in the lubricating oil, heat is further transferred at the pad free walls to the oil by convection. This mechanism causes a thermal gradient in a pad and, consequently, its thermal deflection. In large hydrodynamic thrust bearings, thermal deflection of the pads is an important phenomenon influencing bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Little deviation could be found between those two figures, indicating that the original coarser mesh can be used to obtain a mesh-independent solution of the film temperature. The coarser mesh was also used in the analysis done by Wodtke et al, 27 in which the simulation was performed with FDM. This means that the CBS method could obtain steady-state solution of the energy equation with the same mesh density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little deviation could be found between those two figures, indicating that the original coarser mesh can be used to obtain a mesh-independent solution of the film temperature. The coarser mesh was also used in the analysis done by Wodtke et al, 27 in which the simulation was performed with FDM. This means that the CBS method could obtain steady-state solution of the energy equation with the same mesh density.…”
Section: Resultsmentioning
confidence: 99%
“…The mesh information and the axial load settings could be found in Table 2. The axial loads of Cases 1 and 2 have the same value described in the work of Wodtke et al 27 The hot oil carry-over coefficients, k mix , for oil-lubricated thrust bearings (Cases 1-4) are assumed to be 0.589 based on the work done by Ettles. 24 For Case 5, k mix is assumed to be 0.6.…”
Section: Single-pad Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed description of the model can be found in Refs. [18,19]. The temperature in the lubricated film and in the pad is calculated by solving the 3D energy equation (i.e., the viscosity is varying across the film thickness) and the 3D heat transfer equation, respectively, using the finite difference method.…”
Section: Methodsmentioning
confidence: 99%
“…1 Itaipu thrust bearing pad and support arrangement [18]. In previous works [18,19], the authors completed TEHD analysis of Itaipu thrust bearing without including hydrostatic recess. Comparison of predictions and measurements revealed that there were results discrepancy, especially in the vicinity of the hydrostatic recess.…”
Section: Introductionmentioning
confidence: 99%